DR. BABASAHEB AMBEDKAR AND THOUGHTS ON DEMOCRACY - Ghotekar, Laxman Maroti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Assistant Professor, Department of Political Science, Padmashri Vikhe Patil College of Arts, Science and Commerce, Pravaranagar Email Id- Lmghotekar123@gmail.com Abstract- Dr. Babasaheb Ambedkar has presented various topics like nation and nationalism, religious conversion, independent, political and social democracy, equality, socialism, etc. In a democracy, all people are expected to live in unity. Where there is a difference in the cultural perspective of the people, it is difficult to instill democratic sentiments. This idea is the main idea in Dr. Ambedkar's democratic thought. Caste differences, illiteracy and poverty are the main obstacles in Indian democracy. Until they are destroyed, true democracy will not be able to come into existence in India. According to Dr. Ambedkar, political democracy is also based on four assumptions. 1) The individual is the only one. 2) The individual has certain rights and the constitution must guarantee them to him. 3) In order to obtain any privilege, the individual has to sacrifice his rights. 4) The power to rule over others is not given by the state to any private individual. Dr. Ambedkar was opposed to any form of dictatorship. Because in dictatorship, individual freedom is stifled. The benefit of rights should be given to the maximum number of people. According to Dr. Ambedkar, the best criterion of democracy is 'One person, one value'. The principle of 'One person, one value' is more appropriate.